(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Intrahospital transport means transporting ill patients for diagnostic and therapeutic procedures with in the hospital. Implementation of intrahospital transfer demands a well organized meticulous planning and prompt application of well designed plan. Objectives: To compare intrahospital transportation practices and occurrence of mishaps during intrahospital transport before and after administration of hospital transport guidelines and to determine the association with situational variables (level of floors and distance of destination) Methods: Quasi experimental one group pre test post test design was used in the study by event sampling. 55 pre test transport and 62 post test events were selected. IHT guidelines was given to nurses working in operation theater by using demonstration cum lecture technique, one on one teaching provided to individual nurse consecutively. Observational technique was used for data collection Result showed that the mean percentage of intrahospital practice were higher(89.37%) then pre test (40.03) with a mean difference of 49.33. Computed t value (t=37.46,p=0.000) was statistically significant .Chi square value of occurrence of mishaps regarding intrahospital transport is(X2 =53.9,p=0.001) statistically significant F value between transportation practices with distance from OT were(f=1.68,p=0.16) and Computed t value practices with level of floor were (t=1.60,p=0.39) statistically not significant at 0.05 level of significance. Conclusion Intrahospital transportation guidelines are effective in reducing mishaps and increases transportation practices.